Taxa de performance, volatilidade e retorno nos fundos de ações - Marques, João Moraes da Costa (2012)
This study analyses the effect of charging a performance fee on Brazilian equity funds. Performance fees charged upon investment funds may be regarded as buying a financial call option. In theory, the value of a call option is directly proportional (ceteris paribus) to the volatility of the underlying asset (i.e. the fund quota, in this case). As it is, there is a clear incentive to increase volatility of the quotas of the funds that charge a performance fee. However, on contrary to expectations, the results indicate that those funds that charge a performance fee have presented not only a smaller risk, but also greater efficiency, measured by the relation risk / return.